Alzheimer’s disease pathogenesis and risk factors - Gerulytė , A.; Strumylaitė , L. (Neurologijos seminarai, 2019)
The article reviews the main hypothesis explaining the pathogenesis of Alzheimer’s disease in the formation and accumulation of P-amyloid plaques and neurofibrillary plexus in the brain as well as related theories on the mechanisms of copper and zinc dysregulation, excitotoxicity, cholinergic system dysfunction, and autophagy disorders. The main risk factors for Alzheimer’s disease (increased blood pressure, diabetes, reduced physical activity, brain trauma and the influence of some psychotropic medications) are also discussed.
Keywords: Alzheimer’s disease; dementia; pathogenesis; risk factors